Lacticaseibacillus rhamnosus Probiotics Improve Fasting Blood Glucose, HOMA-IR, and Reduce Body Weight in Diabetic Rat Model - Arresta Vitasatria Suastika; I Gde Raka Widiana; Anak Agung Ngurah Jaya Kusuma; Ni Nengah Dwi Fatmawati; Ketut Suastika; I Nengah Sujaya (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Indonesian indigenous probiotics have been found to improve disruptions of tight junctions in the intestinal epithelium and reduce total cholesterol levels. Improvement in the tight junction could decrease the LPS level and further reduce the blood glucose and insulin resistance. The effects of indigenous Indonesian Lacticaseibacillus rhamnosus (Lr) probiotics on glucose metabolism and inflammatory marker levels in diabetic rats was studied to find if these probiotics are suitable as potential supplementation treatment in diabetes.METHODS: Sixteen female Wistar rats were induced with diabetes using streptozotocin and fed a high-fat, high-sucrose diet. The rats were separated into four groups: LrFBB81, LrFSMM22, LrSKG34, and a control group. Each intervention group got daily dosages of 1 mL probiotic suspensions containing 109 CFU/mL cells given orally for 14 days, whereas the control group received saline. Fasting blood glucose (FBG), insulin, homeostatic model assessment for insulin resistance (HOMA-IR), lipopolysaccharide (LPS), and body weight were evaluated.RESULTS: FBG was significantly reduced in LrFSMM22 group (Δ=120.75 mg/dL, p=0.035), while significant reduction was not observed from LrFBB81, LrSKG34, and control groups. No statistically significant differences were found in HOMA-IR before and after intervention in all groups, but Δ HOMA-IR from LrFSMM22 group was reduced more than the control group (-3.90 vs. 2.02, p=0.028). All groups showed no significant differences in LPS level, meanwhile statistically significant reduction in body weight was observed in all probiotic groups, LrFBB81 (Δ=-15.7 gram, p=0.040), LrSKG34 (Δ= -20.43 gram, p=0.006), and LrFSMM22 groups (Δ=-18.33 gram, p=0.037).CONCLUSION: The administration of L. rhamnosus could improve FBG, HOMA-IR, and reduce body weight without suppressing the LPS.KEYWORDS: diabetes, probiotic, Lacticaseibacillus rhamnosus, fasting blood glucose, HOMA-IR, lipopolysaccharide, insulin resistance